DEVELOPMENT STRATEGY OF MUSIC TOURISM : UBUD VILLAGE JAZZ FESTIVAL AS COMMUNITY-BASED EVENT IN UBUD, BALI - Nungky Puspita (Fakultas Pariwisata Universitas Pancasila, 2021)
Music Tourism is the specialization interest in tourism and this tourism increasing the tourist enthusiasm and attraction. This study describe the Ubud Village Jazz Festival which is the one of the International Music festival that held on Ubud, Bali and also the community-based international music festival . For the analysis, this study use SWOT analyses to make the strategy and the recommendation and also use Elements of Jazz Music Festival theory according to Racapong Khaiewpan. This study use the data from observation and literature study. This research focuses on music tourism attractions and local participation that collaborated in this special event. The results of this study are Ubud Village Jazz Music Festival fulfill the four elements of Jazz Music Festival, for the element of Music Tourism Management in Administrative Aspect this event have so many sponsorships with The Indonesian Creative Economy Agency (BEKRAF), Local brand and business and also with the local people to contributed. For the Music Tourism Management in Design Aspect, this event used Eco-friendly materials. For Marketing Aspect, Ubud Village Festival have sponsorhip with the local TV station to promoting the event. For the Operational Aspect, this event have the schedule and the rules. For Management in Risk Aspect this event have the preparation to discrease the risk for the uncertain weather. The management also advised the tourist to have some preparation to bring raincoat and umbrella because this event is an outdoor event. The local people involved in the whole aspect including the stage of planning, implementation, benefit receipt, monitoring and evaluation which they have done well and organized. Keyword: special event, music tourism, community participation, SWOT analyses